Kajian Teori Sinergi Penggabungan Usaha Bagi Badan Usaha Milik Negara Konstruksi Di Indonesia - Rahmat Fajar Ramdani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The unhealthy financial condition of 7 state-owned construction companies in Indonesia has prompted the Indonesian government to pursue mergers through the Ministry of State-Owned Enterprises. This study analyzes the impact of these mergers on the 7 state-owned construction companies in Indonesia based on the synergy theory. This research is a literature study that uses previous research findings as a basis to reinforce the impact of mergers analyzed based on the synergy theory. According to the results of the literature analysis conducted, the synergy theory suggests that merging the 7 state-owned construction companies can be expected to increase profitability and improve financial health. This is because mergers can enhance efficiency, and market power, and strengthen the companies financial condition.